2022
DOI: 10.21203/rs.3.rs-1464059/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Earthquake sedimentary event record in Early Triassic in southeastern Sichuan Basin, SW China

Abstract: There are some macroscopic and microscopic sedimentary structures of seismic events in the outcrops in Lower Triassic Feixianguan Fm (T1f). and Jialingjiang Fm (T1j). in southeastern parts of Sichuan Basin. The following basic types of sedimentary structures could be observed: Soft-sediment liquefied deformation structures include curled deformation (sliding deformation structure," sausage structure") and microscopic folds (laminated plastic deformation). Seismites emerge in T1f1 and T1f2 in Baimiaozi section,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Laminated thin-layer micritic limestone layer is developed in carbonate tidal flat sedimentary environment in T 1 f 2 at Beibei, Chongqing, and tabular-pebbles with different-size diameters is developed in the lower part of T 1 f 2 wrapping into laminated thin-layer micritic limestone of normal sequences [53]. This tabular-pebbles were defined as the sedimentary products of storm origin in the past [53]. Obviously, storm origin interpretation could not explain why there is no erosion surface and particle sequence in the lower part of tabular-pebbles layer.…”
Section: Tabular-pebblesmentioning
confidence: 99%
See 1 more Smart Citation
“…Laminated thin-layer micritic limestone layer is developed in carbonate tidal flat sedimentary environment in T 1 f 2 at Beibei, Chongqing, and tabular-pebbles with different-size diameters is developed in the lower part of T 1 f 2 wrapping into laminated thin-layer micritic limestone of normal sequences [53]. This tabular-pebbles were defined as the sedimentary products of storm origin in the past [53]. Obviously, storm origin interpretation could not explain why there is no erosion surface and particle sequence in the lower part of tabular-pebbles layer.…”
Section: Tabular-pebblesmentioning
confidence: 99%
“…5). This 'V' shape 'penetration bedding' structure of tabular grave, is triggered by earthquake, making the unconsolidated rock strata in adjacent points broken, and then depositing in the unconsolidated plastic sediments after a short distance transportation with intense disturbance of tsunami and wave [56,57]. Du et al describes this sedimentary structure as rockfall subsidence structure, which represents the quasi in-situ deposition [58].…”
Section: Breccia Of Seismitesmentioning
confidence: 99%
“…The discrepancy of different sedimentary environments reflected by bivalve assemblage and continental vertebrates and plants of the Dongdaqiao Formation was likely caused by a complex sedimentary process influenced by marine and non-marine inputs. Studies on drilling cores in the eastern part of the Qiangtang Basin showed a marine to nonmarine transformation from Triassic to Early-Middle Jurassic [7]. Thus, there is an active debate regarding the origin of Middle Jurassic evaporites in the Qamdo Basin.…”
Section: Introductionmentioning
confidence: 99%